2016
DOI: 10.1016/j.ejpb.2016.03.029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro blood–brain barrier permeability predictions for GABAA receptor modulating piperine analogs

Abstract: The alkaloid piperine from black pepper (Piper nigrum L.) and several synthetic piperine analogs were recently identified as positive allosteric modulators of γ-aminobutyric acid type A (GABAA) receptors. In order to reach their target sites of action, these compounds need to enter the brain by crossing the blood-brain barrier (BBB). We here evaluated piperine and five selected analogs (SCT-66, SCT-64, SCT-29, LAU397, and LAU399) regarding their BBB permeability. Data were obtained in three in vitro BBB models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
(96 reference statements)
0
24
0
1
Order By: Relevance
“…The effect by piperine on FD4 permeation across the RPMI 2650 cell layers did not increase with an increase in piperine concentration over the concentration range investigated (10-50 µM). It was previously proposed that piperine led to polarized paracellular opening of the blood-brain barrier [20] and increased drug absorption by fluidizing the brush border membrane while increasing microvilli length [21]. Furthermore, TEER measurements during the current permeation studies indicated a 8.99, 8.57, and 18.69 % decrease in the presence of 10, 25, and 50 µM piperine, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…The effect by piperine on FD4 permeation across the RPMI 2650 cell layers did not increase with an increase in piperine concentration over the concentration range investigated (10-50 µM). It was previously proposed that piperine led to polarized paracellular opening of the blood-brain barrier [20] and increased drug absorption by fluidizing the brush border membrane while increasing microvilli length [21]. Furthermore, TEER measurements during the current permeation studies indicated a 8.99, 8.57, and 18.69 % decrease in the presence of 10, 25, and 50 µM piperine, respectively.…”
Section: Resultsmentioning
confidence: 72%
“…This parameter completely determines the interaction between the drugs and ABC transporter function (Food and drug administration, 2012;Hubatsch et al, 2007;Kikuchi et al, 2013). To date, only few studies on human BBB cell lines have evaluated this parameter (Eigenmann et al, 2016a;Jähne et al, 2016;Ma et al, 2014). In our model, ER parameter was higher in HBEC-5i with the HA conditioned medium than HBEC-5i alone.…”
Section: Discussionmentioning
confidence: 82%
“…Cependant le premier modèle fondé sur la co-culture de cellules endothéliales progénitrices circulantes en présence d'astrocytes, développé par Boyer-Di Ponio et al [39], présente des niveaux de perméabilité paracellulaire qui sont similaires à ceux de la lignée hCMEC/D3, et donc trop élevés pour étudier les mécanismes de transport/passage de petites molécules au travers de la BHE. En revanche, le modèle développé par Cecchelli et al [12] s'est avéré pertinent pour prédire la distribution cérébrale de petites molécules [12,41] mais aussi pour étudier les capacités de vectorisation de peptides [42], les utiles comme outils de criblage de molécules à destinée cérébrale. Leur utilisation a ainsi permis de réaliser des avancées significatives pour le traitement de la sclérose en plaques et de certaines tumeurs [21,45].…”
Section: Resultsunclassified